High-Risk Behaviors and Associated Factors among Iranian Adult Population: A National Survey - Bahram Ebrahimi; Amin Doosti-Irani; Forouzan Rezapur-Shahkolai; Jalal Poorolajal (Tehran University of Medical Sciences, 2022)
Background: There is no official and representative information on certain health-risk behaviors in Iran. This national survey was performed to determine the prevalence of five high-risk behaviors among the adult population and underlying factors. Methods: This cross-sectional study was performed in 23 provinces of Iran in 2019 involving 10,957 participants. The following five risky behaviors were evaluated: (a) using illicit drugs in the past month, (b) drinking alcohol in the past month, (c) having extramarital sex in the past year, (d) having suicidal thoughts in the past month, (e) and attempting suicide in the past year. The logistic regression model was used for analyses and associations were reported using odds ratio (OR) with its 95% confidence interval (CI). Results: The prevalence of health-risk behaviors was as follows: illicit drug use 10.4%, drinking alcohol 16.8%, extramarital sex 9.9%, suicidal thoughts 8.8%, and suicide attempt 5.4%. Almost 27.6% of the participants were involved in at least one risky behavior. There was a strong association between illicit drugs use and male gender 2.51 (2.11-2.98) and using psychiatric medications 2.96 (2.46-3.55); between drinking alcohol and male gender 2.23 (1.93-2.58); between extramarital sex and divorced/widowed status 2.43 (1.72-3.44) and having an intimate friend of the opposite sex 3.75 (3.13-4.51); between suicidal thoughts and using psychiatric medications 2.23 (1.83-2.72); between suicide attempt and a history of running away from home 2.10 (1.64-2.68). Conclusion: More than one-fourth Iranian adult population is involved in at least one risky behavior. Engaging in any risky behavior may increase the possibility of engaging in other high-risk behaviors.